Rearing behaviour in the mouse behavioural pattern monitor distinguishes the effects of psychedelics from those of lisuride and TBG - Chen, Yahong; Liu, Junhong; Yao, Yishan; Yan, Haitao; Su, Ruibin (Frontiers in pharmacology, 2023)
Psychedelics alter consciousness and may have potential for drug development. As psychedelics are likely therapeutically active, it is important to study their effects and mechanisms using preclinical models. Here, we examined the effects of phenylalkylamine and indoleamine psychedelics on locomotor activity and exploratory behaviour using the mouse Behavioural Pattern Monitor (BPM). DOM, mescaline, and psilocin reduced locomotor activity at high doses and influenced rearings, an exploratory behaviour, in a characteristic inverted U-shaped dose-response function. Pretreatment with the selective 5-HT 2A antagonist M100907 reversed the drug-induced alterations in locomotor activity, rearings, and jumps after systemic administration of DOM at low doses. However, holepoking at the full range of doses tested was not blocked by M100907. Administration of the hallucinogenic 5-HT 2A agonist 25CN-NBOH induced striking similarities in response to that to psychedelics; these alterations were significantly diminished by M100907, whereas the putatively non-hallucinogenic 5-HT 2A agonist TBG did not affect locomotor activity, rearings, or jumps at the most effective doses. The nonhallucinogenic 5-HT 2A agonist lisuride failed to increase rearing. The results of these experiments provide strong evidence that DOM-elicited increases in rearing are due to mediation by the 5-HT 2A receptor. Finally, discriminant analysis was able to distinguish all four psychedelics from lisuride and TBG based on behavioural performance alone. Thus, increased rearing in mice could provide additional evidence of behavioural differences between hallucinogenic and nonhallucinogenic 5-HT 2A agonists.